Penerapan Media Video Pembelajaran pada Kompetensi Membuat Desain Sketsa Sesuai dengan Konsep Kolase di Kelas X SMK Dharma Wanita Gresik - Emmiliana Oktavia Dhaniar; Marniati Marniati (Journal on Education, 2023)
The purpose of this research is to: 1) Determine students' responses after the application of video media, 2) Determine student learning outcomes after the application of video media. This research is a pre-experimental study using a quantitative descriptive method which was conducted in Class X Fashion Design at SMK Dharma Wanita Gresik for the 2021/2022 academic year, with a total of 10 students. Data collection methods used in the form of tests and questionnaires. The results showed that: 1. The students' response to the application of video media received a very positive response with a total average of 4.3, 2. Student learning outcomes after the application of video media were in 100% completeness with student scores ≥75. The findings of this research are that the application of video media to the competency in making sketch designs according to the collage concept in class X Fashion at SMK Dharma Wanita Gresik was declared successful, because students could understand the material better, be enthusiastic, and be active during learning and influence learning outcomes.